Entrepreneurship Workshop: Guide to Successful Entrepreneurship Competitions - Rivani, Rivani; Halim, Hendra; Fadhil, Rahmat; Sitepu, Novi Indriyani; Hanidah, In In; Zikran, Ghrina (Universitas Syiah Kuala, 2025)
The Entrepreneurship Workshop: Guide to Successful Entrepreneurship Competitions was conducted to address the challenges faced by university mentors in providing effective guidance to entrepreneurial students. These challenges include a lack of strategic methods and limited exposure to best practices in entrepreneurship mentoring. The workshop aimed to enhance the competencies of 100 entrepreneurship mentors at Universitas Syiah Kuala by providing practical knowledge and tools.The activity employed a Service Learning (SL) method, integrating theoretical and practical approaches through case-based learning, simulations, and discussions. Participants were introduced to project-based mentoring strategies, digital and financial literacy, and entrepreneurial ecosystems. The workshop also incorporated insights from successful entrepreneurship programs implemented at Universitas Padjadjaran's OoRange Business Incubator.The results showed a significant improvement in participants' understanding and readiness, evidenced by an increase in average pre-test scores from 65 to post-test scores of 85. Additionally, 92% of participants reported high satisfaction with the workshop. The activity has contributed to enhancing mentoring effectiveness and preparing students for entrepreneurship competitions. This initiative supports the development of entrepreneurial ecosystems in universities and aligns with the goals of quality education and economic growth as outlined in the Sustainable Development Goals (SDGs).